New species of Palpimanus Dufour, 1820 from India (Araneae: Palpimanidae, Palpimaninae), with a catalogue of the Indian palpimanid fauna - Tripathi, Rishikesh; Sankaran, Pradeep M.; Kuni, Nikhil; Sudhikumar, Ambalaparambil V. (European Journal of Taxonomy, 2023)
Two new species of Palpimanus Dufour, 1820 are described from India: P. godawan Tripathi & Sankaran sp. nov. (♂♀), collected from the Thar Desert in Rajasthan, and P. maldhok Kuni, Tripathi & Sankaran sp. nov. (♂♀), collected from Maharashtra. Images of the endogyne and male palp of the holotype and paratype of P. narsinhmehtai Parajapati, Hun & Raval, 2021 are presented to facilitate its identification. A key to Indian species of Palpimanus and a catalogue of Indian palpimanid spiders are provided. The current distribution of all the known Indian palpimanid spiders is mapped.